Interprétations de Möise : Égypte, Judée, Grèce et Rome - Borgeaud, Philippe.; Römer, Thomas, 1955-; Volokhine, Youri.; Barbu, Daniel.; Eusebius, of Caesarea, Bishop of Caesarea, ca. 260-ca. 340. (Jerusalem Studies in Religion and Culture, 2010)
The present volume is the result of a team research which gathered biblical scholars, philologists, and historians of religions, on the issue of the multiple \'Interpretations of Moses\' inherited from the ancient mediterranean cultures. The concrete outcome of this comparative inquiry is the common translation and commentary of the fragments from the works of the mysterious Artapanus. The comparative perspective suggested here is not so much methodological, or thematic. It is first of all an invitation to cross disciplinary boundaries and to take account of the contributions of diverse cultures to the formation of a single mythology, in the case, a Moses mythology. With respect to Judea, Greece, Egypt or Rome, and further more an emerging christianity and its \'gnostic\' counterpart, the figure of Moses is at the heart of a cross-cultural dialogue the pieces of which, if they can be seperated for the confort of their specific study, mostly gain by being put together. Ce volume est le fruit d'un travail d'équipe, qui a réuni des biblistes, des philologues, et des historiens des religions autour des multiples « Interprétations de Moïse » que nous ont léguées les cultures de la Méditerranée antique. Le résultat pratique de cette enquête comparatiste culmine dans la traduction et le commentaire à « douze mains » des fragments du mystérieux Artapan, qui ouvrent le volume. Le comparatisme proposé dans le présent volume ne se veut ni méthodologique ni thématique, mais vise d'abord à franchir les frontières disciplinaires, tout en envisageant les apports culturels respectifs contribuant à la formation d'une mythologie, en l'occurrence celle de Moïse. Entre la Judée, l'Egypte, la Grèce, Rome, et bien-sûr le christianisme naissant et l'univers « gnostique » qui l'accompagne, la figure de Moïse est au cœur d'un dialogue, dont les pièces, si elles peuvent être disjointes pour la commodité de l'étude, gagnent surtout à être rapprochées.